Compositional provinces of Mars from statistical analyses of TES, GRS, OMEGA and CRISM data. Issue 1 (26th January 2015) - Rogers, A. Deanne; Hamilton, Victoria E.
Abstract We identified 10 distinct classes of mineral assemblage on Mars through statistical analyses of mineral abundances derived from Mars Global Surveyor Thermal Emission Spectrometer (TES) data at a spatial resolution of 8 pixels per degree. Two classes are new regions in Sinus Meridiani and northern Hellas basin. Except for crystalline hematite abundance, Sinus Meridiani exhibits compositional characteristics similar to Meridiani Planum; these two regions may share part of a common history. The northern margin of Hellas basin lacks olivine and high‐Ca pyroxene compared to terrains just outside the Hellas outer ring; this may reflect a difference in crustal compositions and/or aqueous alteration. Hesperian highland volcanic terrains are largely mapped into one class. These terrains exhibit low‐to‐intermediate potassium and thorium concentrations (from Gamma Ray Spectrometer (GRS) data) compared to older highland terrains, indicating differences in the complexity of processes affecting mantle melts between these different‐aged terrains. A previously reported, locally observed trend toward decreasing proportions of low‐calcium pyroxene relative to total pyroxene with time is also apparent over the larger scales of our study. Spatial trends in olivine and pyroxene abundance are consistent with those observed in near‐infrared data sets. Generally, regions that are distinct in TES data also exhibit distinct elemental characteristics in GRS data, suggesting that surficial coatings are not the primary control on TES mineralogical variations, but rather reflect regional differences in igneous and large‐scale sedimentary/glacial processes. Distinct compositions measured over large, low‐dust regions from multiple data sets indicate that global homogenization of unconsolidated surface materials has not occurred.